Human ecological imperatives of bioremediation for toxic pollution (2003)
The paper is briefly discussed human ecological security as a framework for bioremediation, then expounded on vital components for bioremediation as a response to pollution management from a human ecological security in relation to bioremediation as a technological response to pollution mitigation.These include social justice, environmental integrity, institutional support, economic viability, and social acceptability. It presented ideas and initial definitions of these imperatives from various interest groups. Using the conduct of three bioremediation pilot tests as cases, the paper mapped out the interaction between and among different interest groups involved in the bioremediation pilot testing. The analysis of these interactions generated initial issues pertaining to the identified imperatives.